PEMILIHAN PRESIDEN INDONESIA 2014 DI MEDIA ASING (Studi Kasus New York Times) - Azmi, Alia (Humanus, 2014)
The increasing intensity of international relations and globalization has spurred interests in local events of not only domestic audience but also foreign audience. Some events have become the interest of the public in other countries that the foreign media publish news about the events. The media cover events in a foreign country because the events will influence the government’s foreign policy toward that country. Presidential election leads to the replacement of a country’s leader. Meanwhile, a country’s international relations and foreign policy are influenced by decision making individual such as state and government leader. Personalities, perceptions, activities, and leadership style of the leader influence foreign policy of a country, therefore different leader will make different foreign policy. Indonesian presidential election is covered by foreign media particularly those in countries with good relations with Indonesia. Some Americans pay attention to Indonesian presidential election because it will affect the two countries’ bilateral relation. The New York Times, the most referred print and digital media by American foreign policy makers, also covered the election. Covering the two presidential candidates’ background, the New York Times encouraged the American government to cooperate fully with whoever would be elected, and continue good relation with Indonesia.Key words: foreign media coverage, foreign policy, Indonesia presidential election